2019
DOI: 10.31557/apjcp.2019.20.6.1871
|View full text |Cite
|
Sign up to set email alerts
|

Social Workers in Pediatric Oncology: A Qualitative Study in Iranian Context

Abstract: Background: As professionals, social workers have a special position in relation to considering the needs of children with cancer and their families. Hence, it is important to recognize the experiences and challenges of social workers to improve care of their clients. Method: This study was a qualitative content analysis that aimed to determine a comprehensive understanding of pediatric oncology social workers' experiences in Iran. In total, 19 social workers participated in the study. A purposeful sampling me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 17 publications
0
3
0
2
Order By: Relevance
“…Previous studies confirmed that pediatric oncology social workers are particularly vulnerable to CF and BO (9,(11)(12)(13). Ostadhashemi et al indicated that the involvement of Iranian pediatric oncology social workers in stressful and emotionally demanding situations and facing profes-sional and organizational challenges caused CF and BO (14).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies confirmed that pediatric oncology social workers are particularly vulnerable to CF and BO (9,(11)(12)(13). Ostadhashemi et al indicated that the involvement of Iranian pediatric oncology social workers in stressful and emotionally demanding situations and facing profes-sional and organizational challenges caused CF and BO (14).…”
Section: Introductionmentioning
confidence: 99%
“…Understanding the professional collaboration between health and social workers is crucial as it is a vital part of achieving better patient outcomes, improving patient satisfaction, reducing hospital stays, reducing costs and contributing to fewer and shorter delays in delivery of care (6,7). In addition to managing the medical treatments applied in intensive care units, palliative care centers, and health centers where oncology patients are monitored, it is possible to make assessments of the patient's non-medical needs and psychosocial status with team solidarity (8,9). In the studies conducted, the need for social workers to participate in professional teams in the health sector and palliative care is also strongly discussed (10).…”
Section: Discussionmentioning
confidence: 99%
“…Several strategies were employed to ensure trustworthiness, including allowing participants to familiarize themselves with the topic, checking the data with interviewees, and conducting review and coding [ 26 ] by co-authors who were social work doctoral candidates with expertise in the subject matter [ 27 ].…”
Section: Methodsmentioning
confidence: 99%